Carbon‐Dot‐Induced Acceleration of Light‐Driven Micromotors with Inherent Fluorescence. (4th February 2020) - Wang, Jiajia; Wu, Huiying; Liu, Xiaoya; Liang, Qiying; Bi, Zijun; Wang, Zicheng; Cai, Yuepeng; Dong, Renfeng
Abstract : Real‐time visualization of the positions of micro/nanomotors is highly desired for practical applications due to the complex environments that they are used in. However, most reported photocatalytic micromotors can only be tracked in transparent solutions under bright fields, which greatly limits their applications. Herein, photocatalytic micromotors based on Cu2 O@carbon dot (CDot) particles with excellent fluorescent properties and precise propulsion capabilities in 3D are reported. In the fully green environment of malic acid, the Cu2 O@CDot micromotors display efficient propulsion under visible light irradiation (as high as 40.85 μm s −1 ). In addition, the propulsion direction of the Cu2 O@CDot micromotors can be effectively adjusted by changing the direction of light via positive phototaxis. Interestingly, due to the presence of CDots, these new Cu2 O@CDot micromotors display excellent and stable fluorescence. This study reports the first photocatalytic micromotors with both novel fluorescence properties and excellent propulsion characteristics in biocompatible environments. Due to their excellent fluorescent properties and precise motion control, these Cu2 O@CDot micromotors hold great potential to perform complex tasks across diverse practical applications. Abstract : This work demonstrates photocatalytic Cu2 O@carbon dot (CDot) micromotors with both attractive fluorescence properties and excellent propulsion characteristics in 3D with biocompatible environments. Due to their excellent fluorescent properties and precise motion control, these Cu2 O@CDot micromotors hold great potential to perform complex tasks across diverse practical applications.